PENGEMBANGAN BAHAN AJAR BERBASIS PEMBELAJARAN KONTEKSTUAL DALAM MEMFASILITASI LITERASI SPASIAL SISWA PADA MATERI DIMENSI TIGA - Annisa, Methavia Nurul; Firdausi, Firdausi; Diwidian, Femmy (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractThis research aims to develop modul based on Contextual Teaching and Learning to facilitate spatial literacy among students in SMA/MA in the topic of Three Dimensions which fulfills the criteria of validity, practicality, and effectiveness. The research method used in this study is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. This research uses high school students from the twelfth grade of the Science program at one of the public high schools in South Tangerang City as the subjects of the study, totaling 34 students. Validation was carried out by 3 Mathematics Education lecturers as experts and 5 Mathematics teachers as practitioners. The results of the research indicate that (a) the teaching material is highly valid with a score of 0.905, (b) the teaching material is considered highly practical with a score of 0.872, and the student response questionnaire yielded a score of 0.846, and (c) the teaching material is effective in facilitating students' spatial literacy skills, as evidenced by 79.4% of students achieving scores above the Passing Grade, which is 78. In conclusion, Three-Dimensional teaching materials based on Contextual Teaching and Learning can facilitate spatial literacy among students in twelfth-grade at SMA/MA. AbstrakPenelitian ini bertujuan untuk mengembangkan bahan ajar modul berbasis Pembelajaran Kontekstual dalam memfasilitasi literasi spasial siswa SMA/MA pada materi Dimensi Tiga yang memenuhi kriteria kevalidan, kepraktisan, dan keefektifan. Metode yang digunakan dalam penelitian adalah Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahapan: Analysis, Design, Development, Implementation, dan Evaluation. Penelitian ini menggunakan subjek uji coba yaitu siswa kelas XII IPA di salah satu SMA Negeri di Kota Tangerang Selatan dengan total 34 siswa. Validasi dilakukan oleh 3 dosen Pendidikan Matematika sebagai ahli dan 5 guru bidang Matematika sebagai praktisi. Hasil penelitian menunjukkan bahwa (a) bahan ajar tergolong sangat valid dengan nilai 0,905, (b) bahan ajar dinilai sangat praktis dengan nilai 0,872 dan hasil angket respons siswa memperoleh nilai 0,846, dan (c) bahan ajar efektif dalam memfasilitasi kemampuan literasi spasial siswa, dimana hasil tes menunjukkan sebanyak 79,4% siswa memenuhi nilai KKM yaitu 78. Sehingga dapat disimpulkan, bahan ajar Dimensi Tiga berbasis Pembelajaran Kontekstual dapat memfasilitasi literasi spasial siswa SMA/MA.